Feenberg's Marcuse: Design, Ontology, and the Critique of Technology - Darryl Cressman (Technophany)
A book review of Andrew Feenberg's The Ruthless Critique of Everything Existing: Nature and Revolution in Marcuse's Philosophy of Praxis that emphasizes how Feenberg develops a critical philosophy of technology from Marcuse's work.